Menguak Hikmah Di Balik Ibadah Qurban - Idris Siregar; Ismi Aulia Palem; Naini Anggreini (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The sacrifice of sacrifice is one of the most important acts of worship in Islam. It is mandatory for Muslims who are capable as a form of obedience and obedience to the commands of Allah Swt. Apart from being a form of obedience to Allah Swt, sacrifice also contains social values ​​and concern for others. Through Qurban, Muslims are taught to share their sustenance with other people, especially those who are less fortunate. Therefore, this research aims to describe how the wisdom behind sacrificial worship can provide a deeper understanding of the importance of this worship in the lives of Muslims, as well as how qurban can provide broad benefits for individuals and society as a whole. This research uses the research method used, namely the type of library research or library study, which involves collecting, reading, recording and processing data from various literary sources such as books, magazines and others. The research results show that sacrificial worship has several lessons that cover various spiritual, social, economic and educational aspects. These studies provide a clearer picture of the breadth and depth of the wisdom behind the sacrifice of sacrifice, as well as how this practice continues to be relevant and brings benefits in various aspects of Muslim life.